Study of the reference standard facility of rhodium-iron resistance thermometer - Yin, L.; Lin, P.; Qi, X. (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2014)
A 704 type 4He cryostat is designed and the “National (China) Temperature Working Standard Group of theITS-90 at 1.2–24 K” have been composed. A 703 type 3He cryostat have been established and the working temperature of the “National Temperature Working Standard Group of the ITS-90 at 1.2–24 K” is extended to 0.65 K, which is the lowest limit temperature of ITS-90. The 5 rhodium-iron resistance thermometers (RIRTs) which compose the Working Standard Group have been transformed to the International Temperature Scale of 1990 (ITS-90). A set of indexing data is fitted and calculated as the indexing table of the standard facility of RIRT. 42 basis temperature points have been measured at 0.67–26.37 K. The results show that the temperature control level could reach 0.5 mK/30 min. The difference between the temperature value of the 5 RIRTs and the average is less than 1.1 mK, and the comparison measurements uncertainty is 0.95 mK.